Analisis Perhitungan Jumlah Kebutuhan SDM Menggunakan Metode Workload Indicators of Staffing Need (WISN) di Instalasi Central Sterile Supply Department (CSSD) Rumah Sakit Swasta: Analysis of Calculation of the Number of Human Resources Needs by Using the Workload Indicators of Staffing Need (WISN) Method at the Central Sterile Supply Department (CSSD) Unit of Private Hospital - Dwi Indah Purwanti; Nur Syarianingsih Syam (Universitas Ahmad Dahlan, 2023)
Background: Human resources are a valuable investment for hospitals because they can manage all hospital functions and hospitals are required to provide qualified human resources. One of the human resources in the hospital is CSSD health workers. The purpose of the study was to calculate the number of HR needs using the Workload Indicators of Staffing Need (WISN) method at the CSSD Installation of a Private Hospital. Methods: The research is a type of qualitative research with a case study research design. The research subjects totaled 4 people consisting of observation informants, namely three CSSD health workers and interview informants consisting of two CSSD health workers and the head of SDI staffing. Data collection instruments through in-depth interviews and observations were carried out with a time and motion study approach and calculation of human resource needs using the WISN method. Results: The available work time in the CSSD Installation of a Private Hospital is 138180 minutes per person per year. The highest workload standard in the instrument labeling activity results in a time of 69090 minutes. Standard leeway is 0.08 minutes. The quantity of basic activities amounted to 15387 minutes per year. WISN calculation through a ratio value of 0.6, the number of health workers needed in the CSSD Installation of Private Hospitals in 2023 needed as many as 7 personnel. Conclusion: There is a need for additional health workers as much as 3 personnel from the 4 available personnel.